The meaning of social media for women domestic workers during the Covid-19 pandemic - Nuria Astagini; Billy K Sarwono (Informasi, 2021)
Social media plays an important role during the Covid-19 pandemic, where physical activity and community mobility are limited. Especially for women who work as domestic workers who live with their employers. Social media is the only means for them to connect with the outside world.Previous studies have shown that a person's identity can be shown through the front stage and the back stage. Theoretically, this study analyzing how women domestic workers identify themselves through the online realm using social media. This study uses a constructivist paradigm and a qualitative approach.  The research participants were three women domestic worker who were obtained purposively using the snowball sampling technique. Data was collected through in-depth interviews and observation to participants. The results of the study show that social media allows participants to construct a reality in the online realm that is different from their situation in real life. Therefore, social media has a very important meaning for participants, because with social media, participants feel their position is equal to other users. They also have access to create a front stage and a back stage, where they can create their ideal self-identity. The aspect of self that are presented by the participants on the front stage is individuals who are successful and happy with their lives. For participants, this is an aspect of their ideal self, even though it does not represent their actual state.